2006
DOI: 10.1108/09513540610683711
|View full text |Cite
|
Sign up to set email alerts
|

University and course choice

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
100
0
19

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 260 publications
(124 citation statements)
references
References 10 publications
5
100
0
19
Order By: Relevance
“…Hu and Hossler (2000) found out that tuition fee was directly related to the preference of students in choosing a school. Fee, a component of price, was one of the factors in choosing a school in England (Maringe, 2006). The studies of Jackson (1980) and Pereda et al (2007) also had similar findings.…”
Section: Literature Reviewsupporting
confidence: 67%
See 1 more Smart Citation
“…Hu and Hossler (2000) found out that tuition fee was directly related to the preference of students in choosing a school. Fee, a component of price, was one of the factors in choosing a school in England (Maringe, 2006). The studies of Jackson (1980) and Pereda et al (2007) also had similar findings.…”
Section: Literature Reviewsupporting
confidence: 67%
“…The studies of Jackson (1980) and Pereda et al (2007) also had similar findings. Flexibility of tuition fee payment was also considered (Maringe, 2006). Salahuddin et al (2008) also confirmed through factor analysis that flexibility of tuition fee payment was found to be one of the important factors in choosing a private university.…”
Section: Literature Reviewmentioning
confidence: 72%
“…The choice experiment was based on convenience sampling, in line with and Yu and Cooper (1983), Chiu et al (2005) and Maringe (2006). Although convenience sampling might be subject to some biases, the aim of our study was to uncover variation in preferences.…”
Section: Figure 1 Examples Of Presentations Used In Experimentsmentioning
confidence: 99%
“…A atenção sobre o mercado para a sua futura profissão "[...] está presente nos jovens, não só durante os últimos anos do curso mas também no momento em que estes escolhem a instituição e o curso (Valle & Rebelo, 2001 como citado em Ribeiro, 2008, p. 72). Constata-se, então, que as oportunidades que uma carreira possa oferecer exercem forte influência na escolha de uma formação, implicando planejamento das ofertas pelas instituições de ensino (Maringe, 2006).…”
Section: Referencial Teóricounclassified